11 June 2021: Update on COVID-19 vaccines, vaccine supply, vaccine performance and in-house tests - Nene, Vishvanath M. (International Livestock Research Institute, 2021)
Vish Nene, co-leader of the Animal and Human Health Program at ILRI, gave an update on COVID-19 vaccines, vaccine supply, vaccine performance and in-house tests on 11 June 2021. Find ILRI expertise and resources on zoonoses: ilri.org/zoonoses